Over a million students use our free study notes to help them with their homework
Let's label the equations x2 + y2 = 25 (1) y - x = 1 (2). We can use substitution to solve this simultaneous equation. Let's make y the subject of the equation (2) and we get y = x...
Firstly, you need to get the equation to equal zero, so that you can use the quadratic formula to solve. Therefore you subtract 7 from both sides, meaning the equation becomes: 3x^2+7x-20=0. Recall the qu...
(6x-2)/4 - (3x+3)/3 = (1-x)/3multiply both sides of the equation by 12=lowest common multiple of 4 and 33(6x-2) - 4(3x+3) = 4(1-x)expand brackets18x - 6 -12x - 12 = 4 - 4xsimplifyAnswered by Eleanor L. • Maths tutor2586 Views
So far in your learning it is likely that you have been learnt that if you can't factorise a quadratic equation then you can not solve for x. The quadratic formula is overcomes this restriction, allowing ...
Full Explanation:We have our Equation: y=(x+4)2+7At the turning points, the gradient, (m) is zero m=0 = dy = 0To work out the g...
←
394
395
396
397
398
→
Internet Safety
Payment Security
Cyber
Essentials